RELEVANSI TEORI MASLAHAT DENGAN UU PEMBERANTASAN KORUPSI - Asmawi, Asmawi (De Jure: Jurnal Hukum dan Syari'ah, 2009)
Aiming at protection of religion, soul, intelligence, wealth and progeny, the theory of maslahah permeates the norms of Corruption Eradication Law in Indonesia. The adoption of Islamic criminal law through the theory of maslahah into the system of national law means the transformation and objectivication of the former into the latter, which in turn reflects the integration of Islamic law into national law. The article argues that the application of the theory of maslahah on the criminalization of corruption, the formulation of sanctions on corruption, the concept of responsibility for corruption committted by the corporate, strongly indicates the process of islamization on special criminal law in Indonesia.Bertujuan melindungi agama, jiwa, akal, harta dan keturunan, teori maslahah telah menjiwai norma yang terkandung dalam Undang-undang Pemberantasan Korupsi. Aplikasi hukum pidana Islam melalui teori maslahah dalam sistem hukum nasional mengimplikasikan adanya transformasi dan objektifikasi sistem hukum pertama ke dalam sistem hukum kedua, yang pada gilirannya mencerminkan integrasi keduanya. Artikel ini berargumen bahwa melalui penerapan teori maslahah dalam kriminalisasi korupsi, formulasi sanksi pidana korupsi, dan konsep pertanggungjawaban pidana korporasi jelas menunjukkan terjadinya proses islamisasi dalam perundang-undangan pidana khusus di Indonesia.